Research of chromium (VI) ion adsorption by montmorillonite modified by cationic surfactants - Zhdanyuk, Nataliya (Technology audit and production reserves, 2016)
Montmorillonite has high cation exchange capacity and can be used as a sorbent for the removal of metal cations. But anions adsorption on the surface of the mineral is limited. Targeted regulation of hydrophobic and hydrophilic surface properties using sorbents provides an opportunity to increase its absorption properties in relation to anions. The results show that the degree of Cr(VI) extraction by the sorbents obtained at montmorillonite modification increases with increase of CEC/S. Organoclays that modified at CEC/s 1 showed higher adsorption capacity in relation to Cr(VI), but a part of HDTMA isn’t related to the mineral surface and involved in the removal of Cr(VI) from solution with precipitation in the form of alkyl ammonium chromate. HDTMA in free form is harmful to the environment, so CEC/S for these sorbents must not exceed 1. Adsorption of Cr(VI) compounds essentially depends on pH of a solution. The highest values are obtained at pH from 1 to 6. Adsorption properties of organoclays are decreased at pH 6 to 8. Removal of Cr(VI) is not significant in the alkaline environment. These studies will form the basis for the study of structural and mechanical properties of organoclays to use their suspensions for removal of anions of heavy metals and radionuclides using the latest environmental technologies directly from the soil layers.